Hubungan Intercultural Sensitivity Dengan Efektivitas Komunikasi Dalam Mencegah Bullying di SMA Taruna Nusantara Magelang - Apsari Wahyu Kurnianti; Ascharisa Mettasatya Afrilia (Kanal: Jurnal Ilmu Komunikasi, 2020)
The interaction of each student both in the classroom and in the Taruna Nusantara High School (TN-SMA) dormitory with an Indonesian multicultural background can lead to conflict. One form of conflict is bullying. Bulliying should be avoided if students have effective communication skills. However, before achieving effective communication, it must be known first the level of intercultural sensitivity which is a condition where a person is able to accept the cultural differences that are around him. The purpose of this study was to measure the relationship between the level of intercultural sensitivity and the effectiveness of communication between SMA and TN students. The research method uses quantitative research methods. The correlational research design measures the relationship between intercultural sensitivity and the communication effectiveness of Magelang High School TN students. Data from the research results indicate that there is a relationship between the level of intercultural sensitivity and the effectiveness of communication.